ANALISIS FAKTOR KEBUGARAN JASMANI ATLET FLOORBALL UNESA - EKA PRAYOGA, GANDANG; HIMAWAN SUSANTO, INDRA (Jurnal Kesehatan Olahraga, 2020)
A reliable and professional floorball player doesnt only know about floorball knowledge and mastery. But also must master other fields to achieve the best performance. One of them is to know the level of physical fitness in body readiness when going to do a match. The purpose of this study was to determine the physical fitness factors of Unesa floorball athletes. This type of research is quantitative research with descriptive methods. The population in this study amounted to 80 athletes. While the samples used were 30 athletes using purposive sampling techniques. The research instrument uses a 24-hour food recall form and the Global Tobacco Surveillance System (GTSS) questionnaire. Based on the results of the study showed that as many as 9 athletes by 30% included in the age of 22 years. as many as 15 athletes by 50% included in the sexes of men and women. A total of 11 athletes by 30% are included in the moderate category of diet. As many as 14 athletes by 47% are included in the smoking habit of the former smoker category, only trying to smoke, and passive smokers who are exposed to cigarette smoke every day. A total of 21 athletes by 70% are included in the normal category nutritional status. The results of the physical fitness factors of Unesa floorball athletes are based on physical activity, namely the average physical activity at night due to lifestyle and exercise habits that are done every night. Keywords: Factors of Physical Fitness, Athletes Floorball.